A scoping review of mentor training programs in medicine between 1990 and 2017. Issue 1 (1st January 2019) - Sheri, Krish; Too, Jue Ying Joan; Chuah, Sing En Lydia; Toh, Ying Pin; Mason, Stephen; Radha Krishna, Lalit Kumar
ABSTRACT: Effective mentoring enhances the personal and professional development of mentees and mentors, boosts the reputation of host organizations and improves patient outcomes. Much of this success hinges upon the mentor's ability to nurture personalized mentoring relationships and mentoring environments, provide effective feedback and render timely, responsive, appropriate, and personalized support. However, mentors are often untrained raising concerns about the quality and oversight of mentoring support. To promote effective and consistent use of mentor training in medical education, this scoping review asks what mentor training programs are available in undergraduate and postgraduate medicine and how they may inform the creation of an evidenced-based framework for mentor training. Six reviewers adopted Arksey and O'Malley's approach to scoping reviews to study prevailing mentor-training programs and guidelines in postgraduate education programs and in medical schools. The focus was on novice mentoring approaches. Six reviewers carried out independent searches with similar inclusion/exclusion criteria using PubMed, ERIC, EMBASE, SCOPUS, Google Scholar, and grey literature databases. Included were theses and book chapters published in English or had English translations published between 1 January 1990 and 31 December 2017. Braun and Clarke's approach to thematic analysis was adopted to circumnavigate mentoring's and mentor training's evolving, context-specific, goal-sensitive, learner-, tutor- and relationally dependent nature that prevents simple comparisons of mentor training across different settings and mentee and mentor populations. In total, 3585 abstracts were retrieved, 232 full-text articles were reviewed, 68 articles were included and four themes were identified including the structure, content, outcomes and evaluation of mentor training program. The themes identified provide the basis for an evidence-based, practice-guided framework for a longitudinal mentor training program in medicine and identifies the essential topics to be covered in mentor training programs.